The protective effect of Helicobacter Pylori infection on the susceptibility of multiple sclerosis - Ranjbar, Reza; Karampoor, Sajad; Jalilian, Farid Azizi (Journal of neuroimmunology, 2019)
In recent years, a possible protective role of Helicobacter pylori (Hp) against autoimmune disease has been reported in an experimental murine model of multiple sclerosis (MS), and there are restricted conflicting epidemiologic data concerning Hp serology in MS patients. This study was aimed to determine the seroprevalence of Hp in MS patients and then investigates pro/anti-inflammatory cytokine levels in MS patients infected with HP and seronegative MS patients. Three hundred eighty-seven patients with MS were included in the study and were adjusted by gender and age to 420 healthy subjects. An enzyme-linked immunoassay (ELISA) was used to determine the presence of specific IgG antibodies against H. pylori in the serum sample of both groups. Some pro/anti-inflammatory cytokines levels were evaluated in seropositive/seronegative MS patients and healthy individuals. Our result showed that in patients with MS HP seropositivity was significantly lower than the healthy individual (P < .0001). Also, we showed that HP seropositive MS patients had lower Expanded Disability Status Scale (EDSS) when compared with seronegative MS patients (P < .011). Moreover, we illustrated that proinflammatory cytokine levels include IFN-γ, TNF-α, IL-6, and IL-17 in MS patients infected with HP were lower than seronegative MS patients. Besides, the levels of anti-inflammatory cytokines include IL-4 and IL-10 was significantly higher in MS patients infected with HP when compared with MS patients seronegative for HP infection. In this study, we indicated that HP infection negatively correlated with MS, and conceivably may act as a protective agent against MS. The precise mechanism behind this protective effect remains elusive. However, it seems HP can modulate cytokine signaling, which involved in MS pathogenesis. •HP seropositivity in MS patients was significantly lower than healthy subjects.•EDSS value in seropositive MS patients was significantly lower as compared to seronegative patients.•Proinflammatory cytokines include IFN-γ, TNF-α, IL-6, IL-17 in seropositive MS patients was significantly lower as compared to seronegative patients.•IL-4 and IL-10 in seropositive MS patients was significantly higher as compared to seronegative patients.